Unveiling the Power of Halal Labels, Brand Image, and Price: How Consumer Satisfaction Drives Purchase Decisions - Abelmar, Ryan Farhan; Mansur, Amin (Research of Islamic Economics, 2025)
This study was conducted with the aim of investigating the impact of halal labels, brand image, and price on purchasing decisions, with consumer satisfaction serving as a mediating factor. The study was designed as an explanatory research study. The study population consisted of individuals who use and have used Wardah cosmetic products, with a sample size of 100 respondents. Data was collected using questionnaires and interviews with some respondents. The results of the study indicate that halal labels, brand image and price can be used as models that influence purchasing decisions mediated by consumer satisfaction. Price has a positive and significant effect on consumer satisfaction. Consumer satisfaction has a positive and significant effect on purchasing decisions. Meanwhile, halal labels, brand image and price have a positive but insignificant effect on purchasing decisions. Consumer satisfaction can be a mediator that influences purchasing decisions, but halal labels and brand image are not significant factors. Managerial Implications: The results of this study provide implications for cosmetic companies, such as Wardah, to focus their marketing strategies on increasing consumer satisfaction, as satisfaction has been shown to play a significant role in mediating the influence of price on purchasing decisions.